1. The problem statement

Find a solution of $$\frac{1}{x^2}\frac{\partial u(x,y)}{\partial x}+\frac{1}{y^3}\frac{\partial u(x,y)}{\partial y}=0$$ Which satisfies the condition $\frac{\partial u(x,y)}{\partial x}\big |_{y=0}=x^3$ for all $x$.

2.The attempt at a solution

I get the following general solution for the PDE:


For some function f which satisfies the BC. I'm not too sure how to deal with this type of boundary condition. But here is an attempt:

$\partial_x u=\frac{\text{d}f}{\text{d}z}\frac{\partial z}{\partial x}=\frac{\text{d}f}{\text{d}z} x^2$. Thus $\frac{\text{d}f}{\text{d}z} x^2=x^3\implies \frac{\text{d}f}{\text{d}z} =x\implies f(z)=zx$

At $y=0,~ z=\frac{x^3}{3}\implies x=(3z)^{\frac{1}{3}}$. So $f(z)=(3z)^{\frac{1}{3}}z$.

Changing variables back gives:


This is a solution to the PDE but doesn't satisfy the given boundary condition, it is off by a factor 3/4 and i'm not sure why.

  • $\begingroup$ When you integrated $f'$, you forgot to divide by $4/3$. $\endgroup$ – Rodrigo de Azevedo May 22 '16 at 0:44

If $u (x,y) = f \left(\frac{x^3}{3} - \frac{y^4}{4}\right)$, then the boundary condition gives us $f ' \left(\frac{x^3}{3}\right) = x$. Hence, we have

$$f ' (z) = \sqrt[3]{3z}$$

Integrating, we obtain

$$f (z) = \frac{3\sqrt[3]{3}}{4} \, z^{\frac{4}{3}}$$

and, thus,

$$u (x,y) = \frac{3\sqrt[3]{3}}{4} \left(\frac{x^3}{3} - \frac{y^4}{4}\right)^{\frac{4}{3}}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.